2001
DOI: 10.1177/1077727x01294004
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Sciences Research: A Two‐Decade Comparison, 1980s and 1990s

Abstract: A comparison and assessment of research published in the 1980s and 1990s in the areas of consumer economics, consumption economics, family economics, household management, and family financial planning and counseling was performed. Four journals were selected for this study: Family and Consumer Sciences Research Journal, The Journal of Consumer Affairs, Journal of Consumer Studies and Home Economics, and Journal of Family and Economic Issues. The following pieces of information were extracted from each article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
(2 reference statements)
2
10
0
Order By: Relevance
“…Insufficient insights were available to judge the methodological orientations of the metatheoretical examples shared in the following text, but Reynolds and Abdel-Ghany (2001) found that, for over 25 years, scholarship in the field of FCS has consistently been grounded in the positivistic methodology. The discussion provides evidence of a predisposition toward at least theoretical pluralism in FCS scholarship, defined as the use of a collection of many theories.…”
Section: Fcs Metatheory Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient insights were available to judge the methodological orientations of the metatheoretical examples shared in the following text, but Reynolds and Abdel-Ghany (2001) found that, for over 25 years, scholarship in the field of FCS has consistently been grounded in the positivistic methodology. The discussion provides evidence of a predisposition toward at least theoretical pluralism in FCS scholarship, defined as the use of a collection of many theories.…”
Section: Fcs Metatheory Experiencesmentioning
confidence: 99%
“…Plural methodologies are necessary for the profession to be integrative and forward looking; however, despite the solicitation of alternative modes of inquiry in its official research organs, FCS scholarship does not have a tradition of plural methodologies. Reynolds and Abdel-Ghany (2001) report that scholarship in the FCS discipline has consistently been grounded in the positivistic methodology.…”
Section: Traditions Of Pluralism and Metatheory Within Fcsmentioning
confidence: 99%
“…He identified the societal trends influencing the focus on particular topics and concluded that most research focused on two areas: (a) financial and economic resources and (b) human resources, including time. Reynolds and Abdel-Ghany (2001) reviewed the family, consumer and consumption economics, household management, and family financial planning and counseling research published in four journals during the two decades 1980 to 1999. About the same number of articles (and the same percentage of total articles from all five areas) fit the household management classification in each decade.…”
Section: Research About the Fieldmentioning
confidence: 99%
“…There was a noticeable increase in the use of secondary data research studies. For a detailed assessment of research published in 1980s, see Reynolds and Abdel-Ghany (2001). Another publication outlet, Lifestyles: Family and Economic Issues (currently the Journal of Family and Economic Issues), was launched in 1980.…”
Section: The Decade Of 1970-1979mentioning
confidence: 99%
“…Employment of multivariate techniques was widespread, including ones that were not used in previous decades, such as the double-hurdle model. For a detailed assessment of research published in 1990s, see Reynolds and Abdel-Ghany (2001).…”
Section: The Decade Of 1990-1999mentioning
confidence: 99%